Passivity-Based Control and Current Balance Control of a Current-Source Pulse-Width-Modulation Rectifier - Huarong Zeng; Jianguo Li; Qi Yang; Kui Xu; Xiaohong Ma; Biao Zhao (Energies, 2023)
To improve the static performance, dynamic performance, and current balance of a current-source PWM rectifier with multi-modules, a comprehensive control method with passivity-based control and current balance control is proposed in this paper. Current balance control, which is based on AC voltage sequencing, has the advantages of being easy to implement and not being limited by the number of modules. Mathematical modelling, controller design, and simulation verification were conducted successively, and the results show that the comprehensive control method has a low current impact and high power quality. At the same time, module currents are well balanced, even under external disturbance, when using current balance control.